Reconstitution properties of biologically active polymersomes after cryogenic freezing and a freeze-drying process - Ccorahua R. (2018)
Reconstitution of biologically active polymersomes from the frozen or solid state into any fluid state is still a challenging issue for the design of new biological experiments and for the formulation of therapeutic agents. To gain knowledge about the reconstitution of pH-responsive and photo-crosslinked polymersomes, surface-functionalized and enzyme-containing polymersomers were cryogenically frozen ( 20 C) or freeze-dried with inulin as the lyoprotectant (0.1% w/v) and stored for a defined time period. Reconstituting those polymersomes in solution by thawing or a re-dispersing process revealed their original physical properties as well as their function as a pH-switchable enzymatic nanoreactor.